PENGARUH SELF-CONCEPT DAN LIFESTYLE TERHADAP MINAT BERKUNJUNG PADA DESTINASI WISATA DI KABUPATEN PURWAKARTA - Indra Maulana; Anisya Rachma Kamila (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study was conducted to determine the effect on interest in visiting Purwakarta tourism. In this study, self-concept and lifestyle variables were used as independent variables. Primary data collection using a sample of 100 people. The data analysis method used in this study is multiple linear regression with the help of SPSS 25 software. Based on the results of research that has been done, it shows that partially self-concept and lifestyle have a positive and significant effect on visiting interest. And all independent variables have a simultaneous effect on interest in visiting with a calculated F value of 20,927 with a significance level of 0.000. and the value of R square shows the result of 0.300, which means that all independent variables have a simultaneous effect of 30.0%.